Beef empire carcass merit days index system - Powell, T.H.; Laudert, S.D.; Lee, R.W.; Seibert, G.; Unruh, John A.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Kansas State University, in cooperation with the Beef Empire Days committee, developed a new beef carcass index system for 1991, incorporating yield and quality traits as indicators of carcass merit. Development of the system considered current industry and consumer demands in a critical evaluation of final carcass ranking. The index starts from 100 points and applies positive and negative adjustments for hot carcass weight; ribeye area; adjusted 12th rib fat thickness; percent kidney, pelvic, and heart fat; and quality grade. The index was first used in 1991.
Keywords: Beef; Carcass; Index; Quality; Cutability